Postdural puncture headache incidence with 25G and 27G Quincke needles after spinal anesthesia for elective cesarean section - Biswal, Debadas; Mishra, Jagannath; Sahu, Bimal Prasad; Jena, Shibanee; Smruti Ranjan Nayak (Asian Journal of Medical Sciences, 2023)
Background: Post dural puncture headache(PDPH) is a bilateral occipito-frontal headache occurs in 0.1 to 36% of cases receiving spinal anesthesia. We evaluated the incidence of PDPH after spinal anesthesia using two commonly used needles, 25G and 27G Quincke needles among females undergoing elective cesarean section. Aims and Objectives: The aim of the study was to compare the post-dural puncture headache with 25G And 27G Quincke Needle – in terms of Incidence, severity in patients after spinal anesthesia for elective caesarean section and to find out number of attempts for successful block and any associated complications. Materials and Methods: Six hundred females of ASA grade I or II posted for elective cesarean section under spinal anesthesia were enrolled into two equal groups to assess incidence of PDPH in the post-operative period. They were assessed by a blinded observer for the onset of headache, characteristics, duration, severity, and any associated symptoms for 5 days. PDPH was defined as postural headache that was aggravated by sitting or standing position and relieved by lying supine. Results: The incidence of PDPH was 11% in 25G needle group and 6.33% in the 27G needle group [Risk Ratio of 0.58 (95% CI: 0.34, 0.99)]. In none of the groups, intensity of headache was severe while all were mild in the 27G group. Nausea and vomiting were the only associated symptomatology, 7.33% in the 25G group and 5.67% in the 27G group. Conclusion: The results support 27G Quincke needle to administer spinal anesthesia in females undergoing elective cesarean section.